Urea mediated 5-substituted-1H-tetrazole via [3 + 2] cycloaddition of nitriles and sodium azide. Issue 5 (31st January 2018) - Yakambram, B.; Jaya Shree, A.; Srinivasula Reddy, L.; Satyanarayana, T.; Naveen, P.; Bandichhor, Rakeshwar
Graphical abstract: Highlights: Novel urea azide complex in tetrazole synthesis is identified. Safety challenges associated with tetrazole synthesis are addressed as this method do not employ metal. Alternate pathway for tetrazole synthesis is proposed. Preferred operative mechanism is ascertained by Raman spectroscopy. Abstract: A simple, new and convenient metal free procedure for the synthesis of 5-substituted 1 H -tetrazoles using various nitriles and sodium azide in the presence of urea and acetic acid with good to high yields is developed. The reaction plausibly proceeds through in situ formation of urea azide active complex without toxic and/or expensive metal catalysts.